Quinoxaline 1,4-di-N-Oxides: Biological Activities and Mechanisms of Actions - Cheng, Guyue; Sa, Wei; Cao, Chen; Guo, Liangliang; Hao, Haihong; Liu, Zhenli; Wang, Xu; Yuan, Zonghui (Frontiers in Pharmacology, 2016)
Quinoxaline 1, 4-di-N-oxides (QdNOs) have manifold biological properties, including antimicrobial, antitumoral, antitrypanosomal and antiinflammatory/antioxidant activities. These diverse activities endow them broad applications and prospects in human and veterinary medicines. As QdNOs arouse widespread interest, the evaluation of their medicinal chemistry is still in progress. In the meantime, adverse effects have been reported in some of the QdNO derivatives. For example, genotoxicity and bacterial resistance have been found in QdNO antibacterial growth promoters, conferring urgent need for discovery of new QdNO drugs. However, the modes of actions of QdNOs are not fully understood, hindering the development and innovation of these promising compounds. Here, QdNOs are categorized based on the activities and usages, among which the antimicrobial activities are consist of antibacterial, antimycobacterial and anticandida activities, and the antiprotozoal activities include antitrypanosomal, antimalarial, antitrichomonas and antiamoebic activities. The structure-activity relationship and the mode of actions of each type of activity of QdNOs are summarized, and the toxicity and the underlying mechanisms are also discussed, providing insight for the future research and development of these fascinating compounds.